Community Capacity Building in Funeral Tajhizul Procedures Based on Local Religious and Cultural Values: Peningkatan Kapasitas Masyarakat dalam Tata Cara Tajhizul Jenazah Berbasis Nilai-Nilai Agama dan Budaya Lokal - Fathor Rosi; Sulaiman, Muhammad; Taufiq, Muhammad; Fatholla, Fatholla; Wildan, Labibul (STAI Nurul Huda Kapongan Situbondo, 2025)
The process of managing a deceased person, known as Tajhizul Jenazah, holds significant religious and cultural value in Islamic teachings. This process includes washing, shrouding, performing funeral prayers, and burial according to Islamic principles. However, many communities face challenges due to a lack of understanding and practical skills in conducting Tajhizul Jenazah properly. Additionally, cultural traditions influence the local implementation of funeral rites, necessitating an approach that integrates Islamic values with local wisdom. This community service program aims to enhance the capacity of community members in performing Tajhizul Jenazah by providing educational and hands-on training while respecting local traditions. The program employs a participatory approach, involving religious scholars, community leaders, and local organizations such as the Family Welfare Empowerment Group (PKK). The methodology consists of four key stages: (1) Socialization and counseling to build theoretical understanding, (2) Practical training in funeral management, (3) Simulated exercises with direct mentorship, and (4) Continuous evaluation and monitoring to measure the effectiveness of the program and ensure long-term implementation. The program significantly improved the theoretical knowledge and practical skills of participants. More than 85% of attendees demonstrated an increased understanding of Tajhizul Jenazah, while over 80% successfully performed the procedures according to Islamic teachings. Additionally, the program fostered a greater sense of social responsibility and community engagement, encouraging collective participation in funeral management. The integration of local cultural values further enhanced acceptance and sustainability, ensuring that communities could continue these practices independently.